THE INFLUENCE OF LEADERSHIP STYLE AND WORK STRESS ON EMPLOYEE PERFORMANCE IN HUTA BAYU RAJA SUB-DISTRICT OFFICE - Christina Natalia Hutagalung; Jefry Nando Ginting; Adrian K. Tarigan (International Conference on Health Science, Green Economics, Educational Review and Technology, 2019)
Study This aim For see Influence of Leadership Style and Stress Work on Employee Performance Good in a manner Partial nor simultaneously at the Huta Bayu Raja District Office . Type research used _ is quantitative . Population in study This is employee office sub-district head Huta Bayu Raja, totaling 31 people and determination amount sample in study This that is with make population become sample , however No including Head Camat , the reason that became subject influence in research This is Head Camat . So that sample study This amounted to 30 respondents . Research data sources This is primary data with using research instruments form questionnaire . Method data collection used is survey research . Study This use analysis multiple linear regression For analysis statistics and regression models has tested especially formerly in the assumption test classic . Research results state that testing in a manner Partial Demonstrate Leadership Style influential positive significant on Employee Performance at the Huta Bayu Raja District Office , and testing in a manner Partial show stress Work influential negative significant on Employee Performance at the Huta Bayu Raja District Office . kindly together Leadership Style and Stress Work influential significant on Employee Performance at the Huta Bayu Raja District Office . In t test count 2,923 > 1,703 t table , with mark significant 0.007 <0.05 stated there is influence significant between style leadership to performance employee at Huta Bayu Raja District Office . In t test count -0.773 < 1.703 t table , with mark significant 0.446 > 0.05 declared No exists influence between stress Work to performance employee at Huta Bayu Raja District Office . In the f test count 4.461 > 3.32f table , with mark significant 0.021 < 0.05 stated in a manner together there is influence significant between style leadership and stress Work to performance employee at Huta Bayu Raja District Office . The leadership style used in study This is style leadership democratic , where leader camat always involve employee in every discussion taking decision as well as leaders who don't egotistical and exemplary .